Energy spectra of buoyancy-driven bubbly flow in a vertical Hele-Shaw cell - Ramadugu, Rashmi; Pandey, Vikash; Perlekar, Prasad (Frontiers in Physics, 2023)
We present direct numerical simulations (DNS) study of confined buoyancy-driven bubbly flows in a Hele-Shaw setup. We investigate the spectral properties of the flow and make comparisons with experiments. The energy spectrum obtained from the gap-averaged velocity field shows $E(k)\sim k$ for $kk_d$, and an intermediate scaling range with $E(k)\sim k^{-3}$ around $k\sim k_d$. We perform an energy budget analysis to understand the dominant balances and explain the observed scaling behavior. \MOD{For $kk_d$, the net injection balances net dissipation.} We also show that the Navier-Stokes equation with a linear drag can be used to approximate large scale flow properties of bubbly Hele-Shaw flow.